Development and evaluation of an amorphous solid dispersion-based probucol immediate-release tablet - Adhikari, Vaibhav; Butola, Mansi; Jakhmola, Vikash; Ojha, Abhijeet; Negi, Arvind (Journal of Applied Pharmaceutical Research, 2025)
Background: In its crystalline form, probucol has an extremely low bioavailability and is a poor water-soluble drug. The main aim of this study was to enhance the solubility and dissolution rate of probucol by using a solvent evaporation method to develop a solid dispersion that contains polyvinyl pyrrolidone K30 (PVP-K30) and polyethylene glycol 6000 (PEG 6000). Methodology: The solvent evaporation method is considered superior to other techniques for preparing solid dispersions due to its ability to achieve uniform drug distribution at the molecular level. This method ensures homogeneity by dissolving the drug and carrier in a common solvent, reducing the risk of drug recrystallization and enhancing solubility and bioavailability. Result: The drug-to-carrier ratio is the determining factor for dissolution enhancement. The FTIR spectra do not suggest any chemical interaction between PVP-K30 or PEG 6000. The immediate release profiles of both formulations were favourable, with F3 releasing approximately 95.31% of the drug and F6 releasing around 86.77% within 2 hours. This indicates a rapid drug dissolution, which is beneficial for achieving a fast onset of action and enhancing bioavailability.  Conclusion: The solid dispersion formulations F3 & F6 successfully transformed crystalline probucol to an amorphous state, enhancing solubility & dissolving rates appropriate for immediate-release tablets.